Approach of the patient with a liver mass. Issue 4 (11th August 2012) - Rodríguez de Lope, Carlos; Reig, María E; Darnell, Anna; Forner, Alejandro
Abstract : The widespread use of imaging techniques has led to an increased diagnosis of incidental liver tumours. The differential diagnosis is extremely broad since it may range from benign asymptomatic lesions to malignant neoplasms. The correct characterisation of a liver mass has become a diagnostic challenge for most clinicians. They can be divided in two major categories; cystic lesions, usually benign with excellent long-term outcome, and solid lesions, in which malignancy should be excluded. A particular population is those patients with cirrhosis, who have high risk for hepatocellular carcinoma development. Dynamic imaging techniques have a pivotal role in the diagnostic work-up of liver tumours, allowing a confident diagnosis in most cases. If imaging is not conclusive, a biopsy should be requested to obtain a definitive diagnosis.